Insertional depth-dependent intracochlear pressure changes in a model of cochlear implantation. (1st February 2017) - Mittmann, Marlene; Ernst, Arneborg; Mittmann, Philipp; Todt, Ingo
Abstract: Conclusion: Over time, a homogenous increase in intracochlear pressure was seen in every experiment. Significant reductions in terms of amplitude variation and insertion depth were observed over time, using the one-point-supported insertion method. The frequency of peaks between the thirds was significantly lower when using the two-points-supported insertion method. Objectives: The preservation of residual hearing and minimization of intracochlear trauma are two of the major goals in modern cochlear implantation (CI) surgery. It is assumed that intracochlear pressure measurements yield information about the intracochlear behavior of the electrode itself in the cochlea. The aim of this study was to investigate temporal intracochlear fluid pressure changes using two different kinds of insertion conditions. Method: Cochlear implantations with the Advanced Bionics IJ ® electrode were performed in an artificial cochlear model with a constant insertional speed of 0.5 mm/s provided by a linear actor. Amplitude pressure changes and number of pressure peaks were evaluated for every part. Result: Intracochlear fluid pressure changes are assumed to affect the preservation of residual hearing and should be minimized. The stability and reduction of movement of a lateral wall IJ ® electrode increase at deeper insertion and affect intracochlear fluid pressure amplitude.